Respostas

2013-07-31T17:19:33-03:00
(k-5)(2k-12)\neq0

2k^{2}-12k-10k+60\neq0

2k^{2}-22k+60\neq0

Dividindo-se toda a equação por 2, temos:

k^{2}-11k+30\neq0

\Delta=b^{2}-4\cdot a\cdot c
\Delta=(-11)^{2}-4\cdot1\cdot30
\Delta=121-120
\Delta=1

k\neq\dfrac{-b\pm\sqrt{\Delta}}{2a}

k\neq\dfrac{11\pm\sqrt{1}}{2\cdot1}

k\neq\dfrac{11\pm1}{2}

\Longrightarrow\;k_{1}\neq\dfrac{11+1}{2}=\dfrac{12}{2}=6

\Longrightarrow\;k_{2}\neq\dfrac{11-1}{2}=\dfrac{10}{2}=5

k=]-\infty,\;5[U]5,\;6[U]6,\;+\infty[
1 3 1